2015
DOI: 10.1039/c5ra03331d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite/dextran-functionalized graphene oxide nanosheets for in vivo positive contrast magnetic resonance imaging

Abstract: In vivo positive contrast MRI by magnetite/dextran-functionalized graphene oxide (SPIO-Dex-FGO) as compared to Magnevist® (the right rat).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 53 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…The height profile of the line marked in the AFM image indicates monolayer graphene sheets with 0.8 nm thickness. It is widely accepted that due to the presence of oxygen functionalities on the surface of GO, its thickness is around 0.8-1.1 nm, which is somewhat thicker than the 0.4 nm thickness of graphene sheet [38]. In order to quantitatively evaluate the surface concentrations of carbon-bonded functional groups, the peak area of oxygen-containing bonds and C/O ratio were calculated and inserted in Table 1.…”
Section: Characterization Morphological Images Of the Go Nanosheets mentioning
confidence: 99%
“…The height profile of the line marked in the AFM image indicates monolayer graphene sheets with 0.8 nm thickness. It is widely accepted that due to the presence of oxygen functionalities on the surface of GO, its thickness is around 0.8-1.1 nm, which is somewhat thicker than the 0.4 nm thickness of graphene sheet [38]. In order to quantitatively evaluate the surface concentrations of carbon-bonded functional groups, the peak area of oxygen-containing bonds and C/O ratio were calculated and inserted in Table 1.…”
Section: Characterization Morphological Images Of the Go Nanosheets mentioning
confidence: 99%
“…1,2 In addition, Fe 3 O 4 magnetic nanoparticles (MNPs) have shown promising application as materials of interest for ferrofluids, 3,4 hyperthermia, 5 magnetic resonance imaging (MRI), 6,7 high-density information storage, 8 and targeted drug delivery labeling. 9 A variety of methodologies including coprecipitation, sol-gel method, thermal decomposition, microemulsion and hydrothermal synthesis have been reported for the synthesis of Fe 3 O 4 MNPs, and further advancement in the synthesis of such materials is still on-going due to their outstanding potential in variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous report, negative contrast agents can be improved through modification with dextran to reduce the partial volume effect. In our study, we used a high-resolution MRI machine to achieve the same improvement, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…However, this type of high-resolution MRI machine is expensive and not commonly used in hospitals. Thus, we intend to make further modifications to our nanocomposites to facilitate clinical applications …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation